First record of genus Epicnemis Borgmeier, 1962 (Aenigmatiinae: Phoridae: Diptera) from China, with description of a new species - Chu, Meng-Ying; Liu, Guang-Chun (Zootaxa, 2020)
The genus Epicnemis Borgmeier,1962 is firstly reported from Jiangxi Province, China, with description of a new species, E. linguiformis sp. nov. The new species is distinguished from others of the genus mainly by the structure of the processes on the epandrium.